Novel Diversity of Deeply Branching Holomycota and Unicellular Holozoans Revealed by Metabarcoding in Middle Paraná River, Argentina - Arroyo, Alicia S.; López-Escardó, David; Kim, Eunsoo; Ruiz-Trillo, Iñaki; Najle, Sebastián R. (Frontiers in Ecology and Evolution, 2018)
Opisthokonta represents a major lineage of eukaryotes and includes fungi and metazoans, as well as other less known unicellular groups. The latter are paraphyletic assemblages that branch in between the former two groups, and thus are important for understanding the origin and early diversification of opisthokonts. The full range of their diversity, however, has not yet been explored from diverse ecological habitats. Freshwater environments are crucial sources for new diversity; they are considered even more heterogeneous than marine ecosystems. This heterogeneity implies more ecological niches where local eukaryotic communities are located. However, knowledge of the unicellular opisthokont diversity is scarce from freshwater environments. Here, we performed an 18S rDNA metabarcoding study in the Middle Paraná River, Argentina, to characterize the molecular diversity of microbial eukaryotes, in particular unicellular members of Opisthokonta. We identified a potential novel clade branching as a sister-group to Fungi. We also detected in our data that more than 60% operational taxonomic units classified as unicellular holozoans (animals and relatives) represent new taxa at the species level. Of the remaining, the majority was assigned to the newly described holozoan species, Syssomonas multiformis. Together, our results show that a large hidden diversity of unicellular members of opisthokonts still remain to be uncovered. We also found that the geographical and ecological distribution of several taxa considered exclusive to marine environments is wider than previously thought.